THE PRACTICAL IMPLEMENTATION OF RELAY CONTROL OF CURRENT AS MAIN PART IN SYSTEM OF ACTIVE FILTER OF ELECTRIC POWER - Мещеряков, В.Н.; Хабибуллин, М.М.; Павлов, И.С. (Bulletin of the South Ural State University series "Power Engineering", 2023)
Here is a simple and effective control system of parallel active power filter. This parallel active power filter can improve the quality of the mains voltage when using non-linear loads. This is achieved by a significant reduction in the parallel active power filter harmonic current load and load power factor correction, while avoiding the risk of resonance phenomena typical of passive filters. This control system is a parallel active power filter may be used either in single phase mains or in three phase mains. We offer method of applying developed control system of parallel active filter. Mathematic model of parallel active power filter has been developed in Matlab 7.11, and its modeled results have been shown as obtained from filter performing for active-inductive load. In order to verify the obtained mathematic results of modeling process Matlab 7.11 set up has been designed in order to do research of current relay controller (RCC). On this installation has been confirmed by practical ability to use the RCC as a key element for the creation of the proposed control system is a parallel active power filter.